2020
DOI: 10.1101/2020.10.08.330654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological investigation of reward anticipation and outcome evaluation during slot machine play

Abstract: Slot machines are a popular form of gambling, offering a tractable way to experimentally model reward processes. This study used a 3-reel slot paradigm to assess psychologically distinct phases of reward processing, reflecting anticipation, and early and late-stage outcome processing. EEG measures of winning, nearly missing (a losing outcome revealed at the final, third reel), and “totally” missing (a losing outcome revealed earlier, at the second reel) were collected from healthy adults (n=54). Condition effe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 76 publications
(133 reference statements)
1
5
0
Order By: Relevance
“…2 ( Supplemental Materials ). As reported in ( Fryer et al, 2020 ), HC showed the expected condition effects for SPN, i.e., more negative for anticipated wins than total misses (AA < AB), and the expected condition effects for RewP and LPP, i.e., more positive for wins than near misses (AAA > AAB).
Fig.
…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…2 ( Supplemental Materials ). As reported in ( Fryer et al, 2020 ), HC showed the expected condition effects for SPN, i.e., more negative for anticipated wins than total misses (AA < AB), and the expected condition effects for RewP and LPP, i.e., more positive for wins than near misses (AAA > AAB).
Fig.
…”
Section: Resultssupporting
confidence: 75%
“…3 F; Table S2 ), compared to the HC pattern of greater LPP responses to wins versus near misses ( Fig. 3 E) ( Fryer et al, 2020 ), and the CSZ group, which showed no age-adjusted LPP condition difference.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations